A Study To Assess The Impact Of Cervical Cancer On The Quality Of Life Among Women In Selected Hospital, Puducherry - P, Soniya.; Rajalakshmi, Rajalakshmi (Journal of Neonatal Surgery, 2025)
Background: Cervical cancer remains a major public health concern in India, with profound effects not only on physical health but also on the overall quality of life (QoL) of affected women. Understanding these impacts is crucial for guiding comprehensive care. Objectives: To assess the impact of cervical cancer on the quality of life among women receiving treatment in a selected hospital in Puducherry. Methods: A descriptive cross-sectional study was conducted among 100 women diagnosed with cervical cancer, using purposive sampling. Data were collected through a structured interview schedule, which included demographic and clinical variables along with the Functional Assessment of Cancer Therapy-Cervix (FACT-Cx) tool to evaluate quality of life. Statistical analysis was performed using SPSS version 25, with descriptive and inferential statistics applied. Results: The majority of participants were aged 41–50 years, married, and had low educational status. Most were diagnosed at Stage II and within the past year. Quality of life was reported as moderate by 62% of participants, while 28% had low QoL and only 10% had high QoL. Functional well-being was the most affected domain. Significant associations were found between QoL and variables such as stage of cancer, duration since diagnosis, education level, and type of treatment (p < 0.05). Conclusion: Cervical cancer substantially impairs the quality of life of women, particularly in functional and emotional domains. Holistic care approaches, including psychological support and patient education, are essential to enhance the well-being of these patients. Regular QoL assessments should be integrated into routine oncology practice.